Students' mathematical connection ability reviewed from learning style on Auditory, Intellectually, Repetition learning model - Abdul Hakim, Nailul Fuad; Mulyono, Mulyono (Unnes Journal of Mathematics Education, 2020)
The aims of this study are to (1) comprehensively analyze the achievement of learning completeness of students' mathematical connection ability with the AIR learning model, (2) to find out the improvement in mathematical connection ability with the AIR learning model, (3) to comprehensively analyze the students’ mathematical connection ability with the AIR and DL learning model. , (4) to analyze the difference in the proportion of completeness on the students’ mathematical connection with the AIR and DL learning model, (5) to describe students’ mathematical connection ability on the AIR learning model based on learning style. This research used descriptive quantitative method and class 7 SMP Negeri 16 Semarang for the academic year 2019/2020 became the population of this research. The results showed that (1) the students’ mathematical connection ability on the AIR learning model achieved learning completeness, (2) There was an improvement in the mathematical connection ability of the class on the AIR learning model, (3) the students' mathematical connection ability on AIR learning was better than DL, (4) the proportion of completeness on the test results of students’ mathematical connection ability on the AIR learning was better than DL, (5) the mathematical connection ability reviewed from learning styles was (a) students with the visual learning style met all mathematical connection indicators (b) students with the auditory learning style met three mathematical connection indicators (c) students with the kinesthetic learning style met three mathematical connection indicators